Ferrisiderophore reductase activity in Bacillus megaterium. - Arceneaux, J E (1980)
The release of iron from ferrisiderophores (microbial ferric-chelating iron transport cofactors) by cell-free extracts of Bacillus megaterium was demonstrated. Reductive transfer of iron from ferrisiderophores to the ferrous-chelating agent ferrozine was measured spectrophotometrically. This ferrisiderophore reductase activity (reduced nicotinamide adenine dinucleotide phosphate:ferrisiderophore oxidoreductase) was associated primarily with the cell soluble rather than particulate (membrane) fraction. Ferrisiderophore reductase was inhibited by oxygen and required the addition of a reductant (reduced nicotinamide adenine dinucleotide phosphate was most effective) for maximal activity. The activity was destroyed by both heat and protease treatments and was inhibited by iodoacetamide treatment. Ferrisiderophore reductase activity for several microbial ferrisiderophores was measured; highest activity was displayed for ferrischizokinen, the ferrisiderophore produced by this organism. The Km and Vmax values of the reductase for ferrischizokinen were 2.5 x 10(-4) M and 35.7 nmol/min per mg of the ferrisiderophore reductase reaction. Preliminary fractionation of the cell soluble material by gel filtration chromatography resulted in the demonstration of ferrisiderophore reductase activity in three peaks of different molecular weight. Ferrisiderophore reductase probably mediates entrance of iron into cellular metabolism.